Physically Attractive Women's Experiences of Gender Discrimination in Their Professional Careers (Third Sector Social Economic Review, 2025)
Because of the “beauty is good” stereotype, people who are physically attractive are linked to favorable traits in social interactions, performance reviews, and job decisions. Contrary to the stereotype that “beauty is good”, women who work in male-dominated sectors and are perceived as physically attractive may occasionally experience the impact of “beauty is beastly”. This study explores how physically attractive female captains who work in the male-dominated maritime business describe their experiences with prejudice. Qualitative interviews with female captains on several ships serve as the study's foundation. The study's conclusions demonstrate how gender stereotypes based on female captains' physical attributes restrict women from being deemed qualified for positions requiring technical proficiency. Furthermore, this study provides important insights into how women respond to perceptions that their work is incompatible with their gender and the strategies they adopt to overcome these perceptions.
Keywords: Women seafarers; Femininity; Physical attractiveness; Lack of fit; Beauty is beastly